Insight into the degradation mechanism of fluorene by ferrous/humic acid activated persulfate: Free radical reactions, functional group verification and degradation pathway - Li, Haonan; Liao, Xiaoyong; Li, You; Liu, Qiongzhi; Luo, Junpeng (Frontiers in Environmental Science, 2022)
This study evaluated the performance of humic acid (HA)/ferrous ion (Fe (II)) activating persulfate (PS) for fluorene (FLU) degradation. Results showed that HA/Fe(II)/PS system exhibited the best performance for PS activation to eliminate FLU. Compared to the non-activated case, the degradation efficiency of FLU had increased by 37%-43% in HA activated PS system. HA had significant synergistic effects on Fe (II) activated PS process, but iron ion (Fe(III)) inhibited the degradation. We confirmed that semiquinone radical (SQ·-) acted as the dominant activating group by quenching and electron spin resonance (ESR) experiments, which promoted more radicals generated. The proportion of benzoquinone (BQ) and Fe(II) wielded a considerable influence on FLU degradation, and the optimal concentration ratio was 1:1. Four possible degradation pathways of FLU were deduced, involving ring-opening of the aromatic ring, decarboxylation, oxidative dehydrogenation and hydroxylation, etc.